Impact of Social Determinants of Health on Antiretroviral Therapy among Adolescents Aged Between 10 To 19 Years Living With Hiv In Boro Division In Siaya County - Muchi, Dan (JOOUST, 2022)
Siaya County is one of the five high HIV burden counties in Kenya, with a prevalence of 19.3% among adolescents aged 10-19 years. Evidence suggests that social determinants of health contribute disproportionately to the health outcomes among patients, which can be addressed by reducing health inequities. However, there is limited data in Kenya regarding how social determinants of health affect adolescents living with HIV (ALHIV). The main objective of this descriptive cross-sectional study was to assess the impact of social determinants of health on the uptake of ART therapy, determining its impact on viral load suppression and its outcome on retention among ALHIV aged between 10 to 19 years in Boro Division Siaya County. A purposive sample of 300 was obtained using Krejcie and Morgan table. Quantitative data were summarized using descriptive and inferential statistics (a=0.05), where univariate and multivariate analyses were performed using SPSS version 22, and frequencies were generated for categorical variables. Qualitative data were subjected to thematic analysis. Of the 300 participants, 151 (50.33%) were aged 10-14 years while 157 (52.33%) were female. Being aged 15-19 years (OR = 3.25; p = 0.021), female (OR = 1.87; p = 0.003), recipient of financial support (OR = 3.872; p = 0.001), or living near a health facility (OR = 2.653; p = 0.041) all affected ART utilization. A majority; 195 (65.0%) achieved viral load suppression (<400 copies/ml) and forgetting to take medication was associated by most as the reason for non-suppression at 7 (25.9%). Also being aged 15-19 years (OR = 1.31; p = 0.001), secondary school level of education (OR = 2.194; p =0.042), recipient of financial support (OR = 2.094; p = 0.023), living nearer the health facility (OR =1.892; p = 0.032), taking less than 15 minutes to reach the health facility (OR = 2.084, p = 0.003), waiting time of less than 1 hour (OR = 1.824) or utilization of public transport to reach the health facility (OR = 2.862, p = 0.043) were associated with the likelihood of viral load suppression. Furthermore, being aged 15-19 years (OR = 4.08, p = 0.001), female (OR = 2.093, p =.005), secondary school level of education (OR = 3.093; p = 0.002). Recipient of financial support (OR =2.231; p = 0.024), living nearer the health facility (OR = 1.846; p = 0.015), use of public motorcycle/bicycle to reach the health facility (OR = 1.236; p = 0.021). Taking less than 15 minutes to reach the health facility (OR= 2.084, p =0.005) or waiting time is less than 1 hour (OR= 2.653; p =0.042) all affected retention to ART. Distance from the health facility, long waiting time, level of education, being older (15-19years), being a recipient of financial support, and utilizing public means of reaching the health facility were SDOH that were greatly associated with utilization of ART, viral load suppression and retention to treatment. Understanding these SDOH and mitigating them will help foster individualized services towards ensuring uptake of ART services, HIV viral load suppression, and retention of ART services. Findings from this study will be shared with the County’s department of health and the respective health facilities to help boost the efforts toward adolescent HIV management locally.
Keywords: Antiretroviral Therapy